Pertanggungjawaban Hukum dan Perlindungan Hukum bagi Notaris dalam Membuat Party Acte - Vina Akfa Dyani (Lex Renaissance, 2017)
AbstractThe main problem in this study is the first, how the legal liability by a Notary in making acte party, and secondly, how the legal protection for Notaries in making party acte. This research is a normative juridical research approach to law (statute approach). The data used is secondary data in the form of primary legal materials, secondary and tertiary. The results showed that there are 3 (three) forms of Notary legal responsibility in making acte party, namely the administrative responsibility, civil liability and criminal liability. Notary doing his duty in a responsible manner and in accordance with UUJN and other legislation, the right to protection of the law. Notary legal protection for agency basis given by the Honorary Council of Notaries and Notary Act laws and legal protection through the obligation / right of refusal Notary.Keywords: Responsibility, Protection, Notary and Party Acte. Â